Pengaruh Circuit Training Meningkatkan Kapasitas Vo2max Pada Insan Olahraga - Putri Miftahul Jannah; Ayu Permata; Nova Relida (LPPM Universitas Abdurrab, 2022)
Sport is a daily physical activity to get a healthy and strong body. One of the sports that increase the work of the heart and lungs to the maximum is those which function to increase VO2max given its correlation with aerobic fitness. Soccer requires good aerobic endurance skills. In addition, a high VO2max is highly prioritized since soccer requires good strength and endurance. VO2max is the maximum volume of O2 processed by the body when doing physical activity. If a lot of oxygen is absorbed by the body, the performance of the muscles in contracting is getting better so that the number of residual substances as the cause of fatigue will be decreased. Circuit training improves cardiovascular endurance. This training makes the process of channeling and returning blood to the heart smoother. Aerobic endurance training is needed by sportsperson. One of the efforts to increase VO2Max capacity is through the provision of circuit training interventions. The research subjects consisted of 1 patient who was a sportsperson who liked soccer. This study aimed to determine the increase in VO2max in sportsperson because of the circuit training provision. The study was conducted at the Fit and Rehabilitation Clinic from March 16, 2021, to April 11, 2021. Subjects in the research treatment were given circuit training interventions. The measuring instrument used was the Cooper test. The study was conducted for 12 treatments (T1-T12). Knowing the results of the research that has been done, it was found that the provision of circuit training interventions was able to increase the VO2Max capacity in a sportsperson. This finding is evidenced by an increase in the first Cooper test evaluation before being given the intervention, from 27.47 ml/kg/minute to 40.00 ml/kg/minute on the fifth evaluation after 12 treatments. In conclusion, the circuit training intervention is very effective in increasing the VO2Max capacity.